Future uncertainty and the production of anticipatory policy knowledge: the case of the Israeli future-oriented pedagogy project. Issue 1 (2nd January 2023) - Ramiel, Hemy; Dishon, Gideon
ABSTRACT: This paper explores the production of educational policy discourse based on a view of increasing future unpredictability, focusing on how educational policy knowledge is reconceptualized as a form of anticipatory regime. Specifically, we investigate the Israeli Ministry of Education's Future-Oriented Pedagogy Research and Development Unit, analyzing how the unit produces ways of knowing for policymaking based on the epistemic value of anticipation. Through critical policy analysis of the unit's documents, we explore its structure and rationale, describing two key epistemological mechanisms driving anticipatory educational policy. First, the appeal to 'trends' as a means of generating a certain vision of the future. The centrality of trends establishes a discourse in which policies are subordinated to a future that is at once unpredictable yet inevitable. Second, the introduction of 'adaptivity' as a key educational response to unpredictability, positioning constant change and reaction to external developments as the organizing principle of educational systems.